AB0401 SWITCH FROM ETANERCEPT ORIGINATOR TO ETANERCEPT BIOSIMILAR: DATA FROM REAL LIFE. (June 2019) - Ditto, Maria Chiara; Parisi, Simone; Priora, Marta; Laganà, Angela; Peroni, Clara Lisa; Fusaro, Enrico
Abstract : Background: Biosimilars of antiTNF-α are now available for the treatment of arthritis. There are a lot of data about maintenance of clinical efficacy after switching from originator to biosimilar but also reports about flares and adverse events (AE). Controversies still exist due to ethical and economic reasons. We describe the disease activity trend after switching from etanercept originator (oETA) to its biosimilar (bETA) in a population of Turin, Piedmont, Italy. In this region switch to biosimilar is mandatory by law except in case of patients with history of allergy, off-label, psycological reasons, active disease that required different treatment. Objectives: To evaluate the disease activity trend before and after switch from oETA to bETA. Methods: We switched 82 patients (M/F 33/49, mean age 59.65±11.5, duration of disease 17.56±10.3 years) in stable state of disease from oETA to bETA; 49 patients affected by RA, 24 by PsA, 10 by AS. The mean of duration of oETA and bETA treatment was respectively 129.2 and 6.2 months. We evaluated VAS-pain, Global-Health, CRP, number of swollen and tender joints, DAS28 for RA, DAPSA for PsA, HAQ and HAQ-S, BASDAI for AS patients. Results: Differences of variables between oETA and bETA are summarized in table1 . We didn't find any significant difference between oETA and bETA in order to efficacy. However 8 patients, 5 RA and 4 PsA(9.75%) discontinued bETA because arthritis flare(7) or AE(1). Conclusion: Data about maintenance of efficacy and percentage of discontinuation were similar to the literature. We didn't find significant differences on efficacy after switching from originator to biosimilar. However, considering the rate of flares and AE, further strong studies are required. References: [1] Jørgensen, K. K. et al. Lancet 2017 Jun 10;389(10086):2304-2316. [2] Kay J and KL Winthrop Nat Rev Rheumatol 2017 Jul;13(7):391-392. [3] Toussirot E, Marotte H. RMD Open 2017;3:e000492. Disclosure of Interests: None declared